THE DETERMINANT FACTORS OF OLD SUFFERING DM, BLOOD SUGAR CONTROL, BMI / OBESITY CHRONI COMPLICATIONS OF DIABETES TYPE 2 IN THE ELDERLY - Amir, Faisal (NHM PRESS, 2085)
Diabetes mellitus is a one of chronic disease that can increase rapidly the prevalence ofcomplications in the elderly. The phenomenon that occurs shows that there were still manyelderly who experienced chronic complications of diabetes mellitus. The purpose of this studyis to identify the description of the old factors suffering from DM, blood sugar control,BMI/Obesity, chronic complications of diabetes mellitus tipe 2 in the elderly at the inpatient ofSyarifah Ambami Rato Ebu Bangkalan Regional Hospital.The research design using Analitik Correlative Cross Sectional. The independentvariable in this study was the determinant factor of diabetes mellitus that has old sufferedfrom diabetes,BMI/obesity, blood sugar controlwhile the dependent variable in this study waschronic complications of diabetes mellitus. The number of samples were 56 type 2 DMpatients aged> 60 years. The sample technique used non probability sampling by usingpurposive sampling. instrument research using observation sheets and medical records.Statistical tests using the Spearman Rank Test with (p valve <0.05).The results showed that there was a relationship between the long-standing factor ofDM with chronic complications of diabetes mellitus in old age supported by the theory thatthere were some changes that occurred during the aging process that could facilitate theonset of diabetic neuropathy. Where p valve = 0,000 < 0.05, which means H1 was acceptedand H0 was rejected. This shows that there was a relationship between the length of sufferingfrom DM with chronic complications. This research can be used as material knowledge about the long-suffering factors ofDM, blood sugar control, BMI/Obesity, chronic complications of diabetes mellitus in old ageand for a basis for developing further research such as other factors that have not beenrevealed about the factors that influence chronic complications in the elderly.